Therapeutic hyperthermia for the treatment of infection—a narrative review - Markota, Andrej; Kalamar, Žiga; Fluher, Jure; Pirkmajer, Sergej (Frontiers in Physiology, 2023)
Modulating body temperature, mostly through the use of antipyretics, is a commonly employed therapeutic intervention in medical practice. However, emerging evidence suggests that hyperthermia could serve as an adjuvant therapy for patients with infection. We performed a narrative review to explore the application of therapeutic hyperthermia in the treatment of infection. A number of studies have been performed in the pre-antibiotic era, enrolling patients with neurosyphilis and gonococcal infections, with reported cure rates at around 60-80%. We have outlined the potential molecular and immunological mechanisms explaining the possible beneficial effects of therapeutic hyperthermia. For some pathogens increased temperature exerts a direct negative effect on virulence; however, it is presumed that temperature driven activation of the immune system is probably the most important factor affecting microbial viability. Lastly, we performed a review of modern-era studies where modulation of body temperature has been used as a treatment strategy. In trials of therapeutic hypothermia in patients with infection worse outcomes have been observed in the hypothermia group. Use of antipyretics has not been associated with any improvement in clinical outcomes. In modern-era therapeutic hyperthermia achieved by physical warming has been studied in one pilot trial, and better survival was observed in the hyperthermia group. To conclude, currently there is not enough data to support the use of therapeutic hyperthermia outside clinical trials; however, available studies are in favor of at least a temperature tolerance strategy for non-neurocritical patients.